New insights on the removal of mineral oil from oil-in-water emulsions using cork by-products: Effect of salt and surfactants content - Renata S. Souza (2016)
The present work focuses on the use of two different cork by-products, raw cork (RAC) and regranulated cork (RGC), as sorbents for oil and grease (O&G) removal from mineral oil-in-water (O/W) emulsions (lubricant oil 15W-40). Acidic conditions favored O&G removal from emulsions using cork granules, achieving values of about 90%. RGC showed the highest O&G removal capacity, associated with its thermal treatment with water vapor at 380 degrees C, which increased its hydrophobicity. Sorption isotherms at 25 degrees C were determined at different pH values (2, 4 and 6). Freundlich and linear models were able to fit well the equilibrium data regarding O&G removal using RGC, suggesting that the major sorption mechanism is partitioning (log K-ow around 4.0). Kinetic studies showed that O&G removal rates using RGC were faster (<100 min) than those using RAC (approximate to 1300 min). Moreover, oil sorption onto cork is favored by acidic conditions, achieving values of 90 mg g(-1) at pH 2 (equilibrium oil concentration in the liquid phase of 4.5 mg/L). In order to improve the oil uptake onto regranulated cork at near neutral pH, the use of different salts (NaCl, Na2SO4 and MgCl2) and surfactants (anionic: sodium dodecyl sulfate - SDS, cationic: hexadecyltrimethyl ammonium - HDTMA and nonionic: Tween 80) was tested. The best results were achieved using 0.1 M NaCl and Tween 80. This paper also proposes a mass transfer model based on cork and oil properties, which adequately predicts the kinetic experimental data and attests that the rate-limiting step in the sorption process is the external fluid film resistance.